Multiactor Dynamics in Domestic Wastewater Governance within the Framework of Water Governance - Zahira Syifa Sitoresmi (PCD Journal, 2025)
Wastewater management is important component in sanitation that has direct affect on the quality of clean water sources. This study analyses the implementation of domestic wastewater governance by focusing on two key aspects: government performance and community involvement. Adopting a case study approach, the study was conducted at the Sewon Wastewater Treatment Plant (WWTP), which is the only regional WWTP in the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta/DIY) serving Sleman regency, Yogyakarta city, and Bantul regency. Data were collected through interviews, document analysis, and field observation. The analysis is grounded in a water governance framework, assessing three key dimensions: content, institutional arrangements, and relational dynamics. The results reveal significant gaps in policy implementation, limited coordination among government actors, and minimal public participation. These challenges have negatively impacted the effectiveness and sustainability of domestic wastewater management. Therefore, the study underlines the urgent need for more integrated coordination among governmental bodies and stronger efforts to empower communities. Greater public literacy, involvement in decision-making processes, and inclusive governance practices are essential to improve the performance of domestic wastewater management and ensure long-term environmental sustainability.